2014
DOI: 10.1080/00380768.2014.949852
|View full text |Cite
|
Sign up to set email alerts
|

Radioactive cesium discharge in stream water from a small watershed in forested headwaters during a typhoon flood event

Abstract: We investigated radioactive cesium (Cs) export in stream water during a typhoon flood event (No. 1204, Guchol) in a small forested headwater catchment (1.2 ha), which was contaminated by the Fukushima Daiichi Nuclear Power Plant (FDNPP) disaster. The experimental watershed is covered with hardwood and conifer trees. Hourly stream water samples were collected by an automatic water sampler, and turbidity was measured every 10 min. Downstream transport of radioactive Cs was recorded through the typhoon, during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…In this catchment, the particulate fraction only accounted for 40% of the radiocesium migration in base flow conditions. In addition, Shinomiya et al (2014) found that 92e97% of radiocesium is transferred with the particulate fraction during significant rainfall events (Typhoon Guchol), compared to between 12 and 96% in base flow. From modelling and monitoring research, Mori et al (2014), determined that the particulate fraction transported more than 95% of the 137 Cs, slightly above the range calculated by Yamashiki et al (2014) (82e93%).…”
Section: Radiocesium Distribution Coefficient (Dissolved/particulate)mentioning
confidence: 97%
See 3 more Smart Citations
“…In this catchment, the particulate fraction only accounted for 40% of the radiocesium migration in base flow conditions. In addition, Shinomiya et al (2014) found that 92e97% of radiocesium is transferred with the particulate fraction during significant rainfall events (Typhoon Guchol), compared to between 12 and 96% in base flow. From modelling and monitoring research, Mori et al (2014), determined that the particulate fraction transported more than 95% of the 137 Cs, slightly above the range calculated by Yamashiki et al (2014) (82e93%).…”
Section: Radiocesium Distribution Coefficient (Dissolved/particulate)mentioning
confidence: 97%
“…At the plot or hillslope scale, Yoshimura et al (2015a) determined that between 0.07 and 3.2% of the catchment 137 Cs inventory was exported with wash-off, with a mean annual export of 0.7% for their 7 USLE plots. For a forested experimental catchment, Shinomiya et al (2014) reported that only 0.07% of the initial radiocesium inventory was exported during a typhoon event. In an outline of Fukushima related research projects, indicated that less than 1% of the radiocesium inventory is transferred from hillslopes and discharged from catchments.…”
Section: Monitoring and Modelling Summarymentioning
confidence: 98%
See 2 more Smart Citations
“…Conversely, soil erosion and radiocesium export from forest environments is thought to be limited (Shinomiya et al, 2014;Yoshimura et al, 2015) as a thick litter layer of organic matter covers the soil surface, minimizing rainfall driven soil erosion. A key question for ongoing radiocesium management is whether contaminated forest landscapes represent a potential source of radiocesium to downstream and downslope environments.…”
Section: Introductionmentioning
confidence: 99%